Identification of peripheral CD154+ T cells and HLA‐DRB1 as biomarkers of acute cellular rejection in adult liver transplant recipients. (29th October 2020) - Boix, F.; Legaz, I.; Minhas, A.; Alfaro, R.; Jiménez–Coll, V.; Mrowiec, A.; Martínez–Banaclocha, H.; Galián, J. A.; Botella, C.; Moya–Quiles, M. R.; Sanchez–Bueno, F.; Robles, R.; et al.
Summary: Decreasing graft rejection and increasing graft and patient survival are great challenges facing liver transplantation (LT). Different T cell subsets participate in the acute cellular rejection (ACR) of the allograft. Cell‐mediated immunity markers of the recipient could help to understand the mechanisms underlying acute rejection. This study aimed to analyse different surface antigens on T cells in a cohort of adult liver patients undergoing LT to determine the influence on ACR using multi‐parametric flow cytometry functional assay. Thirty patients were monitored at baseline and during 1 year post‐transplant. Two groups were established, with (ACR) and without (NACR) acute cellular rejection. Leukocyte, total lymphocyte, percentages of CD4 + CD154 + and CD8 + CD154 + T cells, human leukocyte antigen (HLA) mismatch between recipient–donor and their relation with ACR as well as the acute rejection frequencies were analysed. T cells were stimulated with concanavalin A (Con‐A) and surface antigens were analysed by fluorescence activated cell sorter (FACS) analysis. A high percentage of CD4 + CD154 + T cells ( P  = 0·001) and a low percentage of CD8 + CD154 + T cells ( P  = 0·002) at baseline were statistically significant in ACR. A receiver operating characteristic analysis determined the cut‐off values capable to stratify patients at high risk of ACR with high sensitivity and specificity for CD4 + CD154 + ( P  = 0·001) and CD8 + CD154 + T cells ( P  = 0·002). In logistic regression analysis, CD4 + CD154 +, CD8 + CD154 + and HLA mismatch were confirmed as independent risk factors to ACR. Post‐transplant percentages of both T cell subsets were significantly higher in ACR, despite variations compared to pretransplant. These findings support the selection of candidates for LT based on the pretransplant percentages of CD4 + CD154 + and CD8 + CD154 + T cells in parallel with other transplant factors. Abstract : Mechanisms of acute cellular allograft rejection followed liver transplantation employs the activation, proliferation and differentiation of CD4 + CD154 + and CD8 + CD154 + T cells into effector cells triggered by direct allorecognition pathway, which is performed by both but is dominated by CD4 + T cells, and indirect allorecognition pathway virtually restricted to CD8 + T cells·